Piezoelectric Buckled Beam Array on a Pacemaker Lead for Energy Harvesting. Issue 1 (22nd October 2018) - Dong, Lin; Wen, Chunsheng; Liu, Yin; Xu, Zhe; Closson, Andrew B.; Han, Xiaomin; Escobar, Gladys Patricia; Oglesby, Meagan; Feldman, Marc; Chen, Zi; Zhang, John X. J.
Abstract: Self‐sustainable energy generation represents a new frontier to significantly extend the lifetime and effectiveness of implantable biomedical devices. In this work, a piezoelectric energy harvester design is employed to utilize the bending of the lead of a cardiac pacemaker or defibrillator for generating electrical energy with minimal risk of interfering with cardiovascular functions. The proposed energy harvester combines flexible porous polyvinylidene fluoride–trifluoroethylene thin film with a buckled beam array design for potentially harvesting energy from cardiac motion. Systematic in vitro experimental evaluations are performed by considering complex parameters in practical implementations. Under various mechanical inputs and boundary conditions, the maximum electrical output of this energy harvester yields an open circuit voltage (peak to peak) of 4.5 V and a short circuit current (peak to peak) of 200 nA, and that energy is sufficient to self‐power a typical pacemaker for 1 d. A peak power output of 49 nW is delivered at an optimal resistor load of 50 MΩ. The scalability of the design is also discussed, and the reported results demonstrate the energy harvester's capability of providing significant electrical energy directly from the motions of pacemaker leads, suggesting a paradigm for biomedical energy harvesting in vivo. Abstract : A porous piezoelectric buckled beam array is designed on a pacemaker lead, which can harvest cardiac energy by converting the mechanical bending of the lead to electrical charge. The device yields an electrical output of 4.5 V and 200 nA, which is sufficient to self‐power a typical pacemaker for 1 d, suggesting a paradigm for biomedical energy harvesting in vivo.